Unveiling microbial interactions in stratified mat communities from a warm saline shallow pond. (10th May 2017) - Saghaï, Aurélien; Gutiérrez‐Preciado, Ana; Deschamps, Philippe; Moreira, David; Bertolino, Paola; Ragon, Marie; López‐García, Purificación
Summary: Modern phototrophic microbial mats are complex communities often used as analogs of major Precambrian ecosystems. Characterizing biotic, notably metabolic, interactions among different microbial mat members is essential to gain insights into the ecology and biogeochemistry of these systems. We applied 16S/18S rRNA metabarcoding approaches to characterize the structure of archaea, bacteria and protist communities from microbial mats collected along strong physicochemical (oxygen, salinity, temperature, depth) gradients in a shallow pond at the salar de Llamara (Chile). All mats were highly diverse, including members of virtually all known high‐rank eukaryotic and prokaryotic taxa but also many novel lineages. Bacterial candidate divisions accounted for almost 50% of sequences in deeper mats, while Archaea represented up to 40% of sequences in some mat layers. Molecular phylogenetic analyses revealed six novel deeply divergent archaeal groups, along abundant and diverse Pacearchaeota and Woesearchaeota. Multivariate statistical analyses showed that local environmental conditions strongly influenced community composition. Co‐occurrence network structure was markedly different between surface mats located in the oxygenated zone and mats located in transition and anoxic water layers. We identified potential biotic interactions between various high‐ and low‐rank taxa. Notably, a strong positive correlation was observed between Lokiarchaeota and the poorly known candidate bacterial division TA06.